2020
DOI: 10.1155/2020/6644253
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Bioactive Components from Ruellia tuberosa L. on Improving Glucose Uptake in TNF‐α‐Induced Insulin‐Resistant Mouse FL83B Hepatocytes

Abstract: Ruellia tuberosa L. (RTL) has been used as a folk medicine to cure diabetes in Asia. RTL was previously reported to alleviate hyperglycemia, insulin resistance (IR), abnormal hepatic detoxification, and liver steatosis. However, the potential bioactive compounds of RTL have still not been identified. The aim of this study was to investigate the bioactive compounds in RTL ethyl acetate (EA) fractions by using a glucose uptake assay in TNF-α-treated mouse FL83B hepatocytes to discover a mechanism by which to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…Although this compound is speculated, the components are quite complicated. Our recent study indicated the possible bioactive compounds of EA from RTL identified by high-performance liquid chromatography assay, including phenolic acids (syringic acid and p-coumaric acid) and flavanoid (cirsimaritin) on improving glucose uptake in hepatocytes [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although this compound is speculated, the components are quite complicated. Our recent study indicated the possible bioactive compounds of EA from RTL identified by high-performance liquid chromatography assay, including phenolic acids (syringic acid and p-coumaric acid) and flavanoid (cirsimaritin) on improving glucose uptake in hepatocytes [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The IR-induced paradigm was described as the previous method with slight modifications [ 10 ]. FL83B cells were seeded in 10 cm dishes and incubated at 37°C for 48 h to reach 80% confluence.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ruellia tuberosa L. is broadly spread in Asian countries, i.e., Indonesia [ 6 ]. In traditional remedies, this flora is recognized as an antidiuretic, antidiabetic, analgesic, and antihypertensive [ 7 – 9 ].…”
Section: Introductionmentioning
confidence: 99%